PENGEMBANGAN TES KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI HUKUM NEWTON DI SMP - Muna Ulfah; Tomo Djudin; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe study aims to create an appropriate critical thinking skills test to assess the critical thinking skills of Newton’s Law material in junior high. The research was obtained through the Research and Development method of Borg & Gall, it was simplified into five stages, including initial data collection, planning, product design, a small-scale trial, and revision of small-scale trials.  The research subject was23 students in Junior High School 3 Sungai Raya, Bengkayang Regency. The instrument was a multiple-choice objective test. The finding showed that within 15 items there were 5 feasible items developed based on developmental procedures, a good test quality, and details of test quality, including: (1) produces six valid items with a correlation coefficient of r count of 0,426 - 0,712; (2) produces six reliable items with a correlation coefficient of r11 of 0.607; (3) produces 10 good questions with a TK index of 0.35 - 0.70; and (4) produces 8 good items with a DP index of 0.273 - 0.727. This critical thinking ability test is expected to be one of the tools to measure critical thinking skills in learning science in junior high school. Key words: Critical Thinking Skills, Newton’s Law, Test Development